1994
DOI: 10.1002/amo.860030115
|View full text |Cite
|
Sign up to set email alerts
|

Laser processes in wide gap II–VI semiconductors

Abstract: After a brief historical remark about the evolution of scientific interest in wide gap Il-VI compounds, we review the various laser processes which have been identified in bulk materials and thin layers during the last 25years. We then proceed to quantum wells and superlattices and stress the differences from Ill-V compounds. We finish by considering the exploitation of specific properties of widegap Il-VI compounds for light-emitting and laser diodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 45 publications
1
5
0
1
Order By: Relevance
“…Spontaneous and stimulated emissions of free excitons [22][23][24] Excitonic emissions in ZnO single crystals had been intensively studied for over three decades. The attentions have mainly been focused on the excitonic process at cryogenic temperatures [9,10,25,26]. The large exciton binding energy ($60 meV) in ZnO should, in principle, favor efficient excitonic emission at room temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spontaneous and stimulated emissions of free excitons [22][23][24] Excitonic emissions in ZnO single crystals had been intensively studied for over three decades. The attentions have mainly been focused on the excitonic process at cryogenic temperatures [9,10,25,26]. The large exciton binding energy ($60 meV) in ZnO should, in principle, favor efficient excitonic emission at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…these nano-crystallite films originates from different recombination process depending on the pumping intensity. Stimulated emission can arise through various excitonic recombination processes, such as, exciton molecule (bi-exciton), exciton-exciton collision, exciton-electron collision, and exciton-optical phonon scattering [10,26]. We attribute the P lasing band at room temperature to the radiative recombination process of the exciton-exciton collision because of the following facts: (1) The intensity of the P band below the threshold increases quadratically with the increase of pumping intensity (Fig.…”
Section: Article In Pressmentioning
confidence: 99%
“…56 However, semiconductor nanowires often suffer from a relatively large waveguide loss and high lasing threshold (B100 mJ cm À2 ) due to their inherent level structure for exciton interband transition that is accompanied with a large self-absorption. 57,58 Even worse, the Wannier excitons are usually unstable in inorganic semiconductors because of their low exciton binding energy (B10 meV), and thus would result in severe non-radiative recombination and low photoluminescence (PL) efficiency at room temperature.…”
Section: Singlet Exciton Stimulated Emission For Low-threshold Nanowi...mentioning
confidence: 99%
“…Besides the EHP excitonic scattering processes cause also stimulated emission in the direct semiconductors due to the dependence of the effective density of states or of the Mott density on material parameters like the dielectric constant, the effective masses, and thus on the excitation conditions [6]. No comprehensive study of such processes in epitaxial ZnTe/GaAs layers has been reported yet.…”
Section: Introductionmentioning
confidence: 99%